Die grosse Abweichungen für die homogenen Markoffschen Kelten - Aleškevičienė, A. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Алешкявичене. Большие уклонения для однородных цепей МарковаA. Aleškevičienė. Dideli atsilenkimai homogeninėms Markovo grandinėms